Paintingdigitalphotography : synthesis and difference in the age of media equivalence - Robinson, Carl, 1958- (Cambridge Scholars Publishing, 2018)
We live in a digital age where the mediums of art are inextricably bound to the binary code, and painting and photography are redefined in their interconnected relationship through digital reconfiguration. As digitisation unmoors these mediums from their traditional supports, their modes of production, display and dissemination shift. These changes bring about new ways of creating, and engaging with, artworks. Through this, the innate qualities of the mediums, previously anchored in their analogue nature, are re-evaluated through their connection with the digital. Born out of the PaintingDigitalPhotography conference, held at QUAD Derby, UK, in May 2017, this anthology of essays investigates aspects of interconnectivity between painting, digital and photography in contemporary art practices. It contributes to critical discourses around networks of associations by examining where syntheses occur, and differences remain, between these mediums at the beginning of the twenty first century.